How are elderly patients treated after a diagnosis of metastatic colorectal cancer in real‐life practice? A study in a French teaching hospital. (5th October 2016) - Gouverneur, Amandine; Rouyer, Magali; Grelaud, Angela; Robinson, Philip; Colombani, Françoise; Terrebonne, Eric; Smith, Denis; Fourrier‐Réglat, Annie; Noize, Pernelle
Abstract: Metastatic colorectal cancer (mCRC) is frequent among elderly patients. However, in the era of new targeted therapies, little is known about real‐life mCRC treatment in this population. This study aimed to describe elderly mCRC patients and the current real‐life treatment practices. mCRC patients aged ≥65 years were identified using the registry of multidisciplinary team meetings, mandatory for all cancer patients, held between January 1, 2013 and June 30, 2014 at the Bordeaux University Hospital. Data were collected from medical records using a standardized questionnaire. Treatment type was defined as follows: at least one anticancer medication administered vs. best supportive care (BSC). A total of 78 patients were included; median age was 74 years and the M/F sex ratio 1.6. Eleven patients (14.1%) were referred to a geriatric oncology consultation. One patient died before treatment initiation, 28 (35.9%) had BSC, and 49 (62.8%) were treated with anticancer medications: 20 (25.6%) had chemotherapy combined with a targeted therapy, and 28 (35.9%) chemotherapy alone (one missing data for treatment). Compared to patients treated with anticancer medications, BSC patients were older ( P < 0.0001) and had more often metachronous metastases ( P = 0.01), more comorbidities ( P = 0.05), and a greater number of concomitant medications ( P = 0.004). This study is one of the rare investigations providing insight to treatment practices in all elderly mCRC patients, not just those who receive anticancer medications. Our results suggest that efforts must be pursued to better integrate geriatric oncology in daily clinical practice.